PERANCANGAN PERAHU BERBAHAN FIBER GLASS BERLAPIS KARET UNTUK EVAKUASI BENCANA BANJIR - Purwo Joko Suranto; Iswadi Nur (Bina Teknika, 2017)
Most of territory in DKI Jakarta that affected by floods. The floods subscription areas are flooded with varying depths, range from 0.5 meters to 3 meters. The habits of the people affected by the flood are reluctant to evacuate if the flood height is still below 0.5 meters, The flood victims want to evacuate after the flood has reached depth above 1 m. At the height of the flood above 1 m it will be difficult to evacuate to a safer place, because the water level is high and can dangerous for their livesThus the required means of transportation that can evacuate the flood victims quickly and safely. The design of the boat using rubber-coated Fiber Glass material for the evacuation of flood disaster, its size determination can be adjusted into the Narrow alley that are at least 2 meters wide.Boats are designed with speed 6 knots, hull construction with double hull construction. In the design calculate the strength, load, resistance, main engine and also the stability for passenger safety can be guaranteed. To ensure the safety of passengers in case of unwanted things, then the boat is equipped with life jackets.